STRESS MANAGEMENT AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORKPLACE MOTIVATION IN MANUFACTURING INDUSTRIES IN NORTH CENTRAL NIGERIA - Hian, Fabian Terkura; Eya, Criscent Ike; Damsa , Justin Terris (The journal of contemporary issues in business and government, 2025)
This study examines the impact of stress management on employee performance, with workplace motivation as a mediating variable, in manufacturing industries in North Central Nigeria. The specific objectives are to assess the direct relationship between stress management (independent variable) and employee performance (dependent variable), evaluate the mediating role of workplace motivation, and explore the factors influencing stress management and its effectiveness. Drawing on the Job Demands-Resources (JD-R) model and Herzberg’s Two-Factor Theory, the study provides a theoretical basis for understanding how workplace motivation interacts with stress management to influence performance. A descriptive research design will be employed, using a quantitative methodology. Data was collected through structured questionnaires distributed to employees in selected manufacturing firms across North Central Nigeria. The Structural Equation Modeling (SEM) technique will be applied for data analysis to test direct and indirect relationships among variables. Results reveal that workload management WL (coefficient = 3.5013, SE = 0.0269, z = 130.35, p < 0.001) and work-life balance WB (coefficient = 8.2682, SE = 0.1146, z = 72.15, p < 0.001) significantly enhance Workers’ motivation WM, while support systems SS (coefficient = 0.0395, SE = 1.1592, z = 0.03, p = 0.973) shows no meaningful impact. WM mediates the relationship between WL, WB, and EP, significantly predicting EP (coefficient = 0.9116, SE = 0.2762, z = 3.30, p = 0.001). Indirect effects confirm workload management (coefficient = 3.5038, z = 535.86, p < 0.001) and work-life balance (coefficient = 3.4185, z = 134.15, p < 0.001) as pivotal contributors to Workers’ motivation, which in turn influences employee performance. However, support systems lacks significant direct or indirect effects, suggesting limited relevance in the current model. Workload management and work-life balance are key drivers of workers’ motivation, a critical mediator for improving employee performance. Support systems require reevaluation to enhance their organizational impact. It is recommended among others that business organizations should optimize workload distribution, foster work-life balance, and focus on enhancing workers’ motivation through recognition programs and career growth opportunities.